Perancangan User interface Website Untuk Promosi Paw Paw Cafe Dengan Metode Design thinking - Erico, Muhammad; Wicaksono, Arif Ranu (Visualita Jurnal Online Desain Komunikasi Visual, 2024)
This research aims to design the user interface (UI) of the Paw Paw Cafe website as a more modern and professional promotional media using the design thinking method. The cafe industry in Surakarta City, including Paw Paw Cafe, which has an animal theme, is experiencing rapid growth. However, cafe promotion is still limited to social media. This research aims to design the user interface (UI) of the Paw Paw Cafe website as a more modern promotional media that has a professional and formal impression. This will increase customer trust and loyalty. In developing the UI of this website, the design thinking method is used, which is well known for its effectiveness because it can combine empathy, creativity, and analysis to solve problems in creating a website. The design thinking method includes empathizing, defining, ideating, prototyping, and testing. In testing the UI of the Paw Paw Cafe website, which involved 20 respondents consisting of cafe managers and customers, positive results were obtained; more than 85% of respondents stated that it was good in terms of speed of access, completeness of information, ease of use for navigation, attractive appearance of the website UI and UI. The Paw Paw Cafe website can function well.